2016
DOI: 10.1515/rmeef-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking and Financial Development

Abstract: With the growing number of Islamic banks worldwide, much ink has been spilled on heated debate about its merits and ability to improve the financial sector. In order to buttress the subject matter of this debate, this paper investigate the link between Islamic banking assets share and the financial development. Using five different proxies of financial development from 22 countries for the period between 2000 and 2013, this research employs the generalized method of moments to cope with the endogeneity problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…They argue that engagements of IBs in Malaysia are mostly non‐participatory, whose effects are mostly short‐term. Lebdaoui and Wild (2016) empirically analysed whether EG is sensitive to Islamic banking presence in selected Southeast Asian economies. Utilizing panel auto‐regressive distributed lag approach, they ascertained that in the long‐run EG exhibit sensitivity towards Islamic banking presence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argue that engagements of IBs in Malaysia are mostly non‐participatory, whose effects are mostly short‐term. Lebdaoui and Wild (2016) empirically analysed whether EG is sensitive to Islamic banking presence in selected Southeast Asian economies. Utilizing panel auto‐regressive distributed lag approach, they ascertained that in the long‐run EG exhibit sensitivity towards Islamic banking presence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The underlying premise of these studies is that, if Islamic banks are demonstrated to be more efficient, more stable, and more profitable and their financing behavior less procyclical, they would contribute more positively to the well-functioning of the financial system and, consequently, the health of the economy. Recent studies have also directly assessed the roles of Islamic banks in financial and economic development (Gheeraert, 2014;Gheeraert and Weill, 2016;Imam and Kpodar, 2016;Lebdaoui and Wild, 2016). We add to this literature by bringing to the fore the issue of financial intermediation costs.…”
mentioning
confidence: 99%
“…Gheeraert (2014) finds that Islamic banking contributes positively to banking sector development and exerts no crowding-out effect on conventional banking system. Lebdaoui & Wild (2016) further firms up the positive link between financial development and Islamic banking presence. Assessing Malaysian experience, Kassim (2016) documents positive effect of Islamic banking development on economic growth.…”
Section: Islamic Banking Presencementioning
confidence: 90%
“…Abedifar et al (2016) use the asset share of Islamic banks in their assessment of the roles of Islamic banks in funding mobilization, economic growth, inequality and poverty. Likewise, Lebdaoui & Wild (2016) use the asset share of Islamic banks in their analysis of financial development. Gheeraert (2014) and Imam & Kpodar (2014) employ three alternative measures of Islamic banking, the sizes of Islamic banking assets, financing and deposits relative to GDP.…”
Section: Methodsmentioning
confidence: 99%